2013
DOI: 10.2134/jeq2012.0251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bedding Materials on Concentration of Odorous Compounds and Escherichia coli in Beef Cattle Bedded Manure Packs

Abstract: The objectives of this study were to determine the effect of bedding material (corn stover, soybean stover, wheat straw, switchgrass, wood chips, wood shavings, corn cobs, and shredded paper) on concentration of odorous volatile organic compounds (VOC) in bedded pack material and to determine the effect of bedding material on the levels of total in laboratory-scaled bedded manure packs. Four bedded packs of each bedding material were maintained for two 6-wk periods ( = 64). Straight- and branched-chained fatty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
35
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(58 citation statements)
references
References 46 publications
20
35
2
1
Order By: Relevance
“…Previous research has demonstrated that certain physical and chemical properties of the bedded manure packs are correlated to the concentration of odorous VOCs in the manure packs, but the concentration of total E. coli was not affected by the chemical and physical properties measured (Spiehs et al, 2013). Free air space, bulk density, lignin, pH, and total sulfur content were negatively correlated to the concentration of odorous VOCs in the bedded pack material (Spiehs et al, 2013). However, measurements were not taken to evaluate odorous VOCs emitted into the air from the bedded packs or to determine how physical and chemical properties correlate to the concentration of the volatilized VOCs.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has demonstrated that certain physical and chemical properties of the bedded manure packs are correlated to the concentration of odorous VOCs in the manure packs, but the concentration of total E. coli was not affected by the chemical and physical properties measured (Spiehs et al, 2013). Free air space, bulk density, lignin, pH, and total sulfur content were negatively correlated to the concentration of odorous VOCs in the bedded pack material (Spiehs et al, 2013). However, measurements were not taken to evaluate odorous VOCs emitted into the air from the bedded packs or to determine how physical and chemical properties correlate to the concentration of the volatilized VOCs.…”
mentioning
confidence: 99%
“…Spiehs et al (2013) measured concentrations of odorous volatile organic compounds (VOCs) in beef cattle bedded manure packs when corn stover, soybean stover, wheat straw, switch grass, pine wood chips, pine wood shavings, pelleted corn cobs, and shredded paper were used as bedding. Corn cob bedding had the highest concentration of odorous VOCs, and pine wood shavings had the lowest.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Both short-term (less than 1 year) and long-term storage (more than 1 year) may occur, but in either case, carbon availability decreases, and protein fermentation increases, as indigenous microorgan isms in the manure continue to metabolize the material (21). When such aged manure is subsequently used in composting mixtures, the materials either take longer to heat or their maximal temperatures are lower than if the composting mixtures had been prepared with fresh manure (1,14).…”
mentioning
confidence: 99%
“…Scientific research has identified several aspects of agricultural practice as major sources of pungent pollutants that contaminate our atmosphere, including feeding and rearing livestock, as well as composting their waste (Akdeniz et al, 2012;Hottenstein and Ana, 2008;Smet et al, 1999). The environmental significance of numerous farmed animal sources has been documented; for example, beef (Spiehs et al, 2013;Shabtay et al, 2009) and dairy cattle (Parker, 2008;Hayes et al, 2006), swine (Parker, 2011;Lim et al, 2004), and poultry barns (Dunlop et al, 2010;Hayes et al, 2006;Carey et al, 2004). Likewise, the production and use of animal feed Montes et al, 2010) and application of manure are also crucial factors in the release of malodors from agricultural activities into the air.…”
Section: Introductionmentioning
confidence: 99%